Immunization of Broiler with Dead Sporozoites as Vaccine Against Eimeria tenella Parasite - Al-Idreesi , Suhair R.; Kweider, Mahmoud; Katranji, Mahmad M. (International Journal of Poultry Science, 2013)
Chickens were protected against coccidiosis induced by Eimeria tenella by using 125, 000 dead sporozoites that were injected in neck subcutaneously with two doses at 3rd and 16th days of age. Efficacy of this vaccine was estimated after challenge by determination some parameters like protection rate which was around 96.1-96%. Number of oocysts and cecal lesion score from the chickens in the immunized groups were decreased significantly (p